2014
DOI: 10.1074/jbc.m114.561845
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MicroRNAs in the Regulation of Muscle Wasting during Catabolic Conditions

Abstract: Background: MicroRNAs are important modulators of gene expression but their role in the atrophy program and in muscle loss is unknown.Results: miRNA-206 and miRNA-21 are critical for regulation of the atrophy program after denervation.Conclusion: miRNAs are important for the fine-tuning of the atrophy program.Significance: Modulating miRNA expression is a novel potential therapeutic approach for counteracting muscle loss and weakness in catabolic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
156
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(162 citation statements)
references
References 64 publications
5
156
0
1
Order By: Relevance
“…Based on the recent data by Soares et al . (2014), we hypothesize that microRNA‐143 function, as well as Igfbp5 regulation, is context dependent; specifically, miR‐143:Igfbp5 interactions in the satellite cells during aging are likely to be among the key interactions regulating the balance between cell viability and senescence during aging, whereas in other scenarios, such as diabetes or cachexia, Igfbp5 genes may be regulated by a different set of microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the recent data by Soares et al . (2014), we hypothesize that microRNA‐143 function, as well as Igfbp5 regulation, is context dependent; specifically, miR‐143:Igfbp5 interactions in the satellite cells during aging are likely to be among the key interactions regulating the balance between cell viability and senescence during aging, whereas in other scenarios, such as diabetes or cachexia, Igfbp5 genes may be regulated by a different set of microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-1 appears to interact with FoxO3a activity through HSP72 during dexamethasone-mediated muscle atrophy (36). miR-206 is upregulated by denervation-induced atrophy in mice skeletal muscle, and inhibition of miR-206 partially protects the atrophy (68). miR-208b (9) and miR-499 (2) can potentially repress the expression of myostatin, a well-known negative regulator of muscle growth (58).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data in the study suggested that a posttranscriptional regulation by microRNA (miRNA) might be associated with the activating process of the ubiquitin-proteasome system. The discovery of miRNAs has provided a new aspect that could expand our knowledge to understand the mechanisms of skeletal muscle atrophy (68,77). Therefore, we also aimed to evaluate the possible involvement of these molecules in AMPK-mediated regulation of muscle mass during hindlimb unloading.…”
mentioning
confidence: 99%
“…Of note, some muscle specific miRNAs (also called myomiRs), such as miR 1 and miR 133, were reported to have roles in both cardiac hypertrophy and muscle atrophy 4 . Interestingly, miR 21, which critically con tributes to cardiac fibrosis, has been shown to promote muscle wasting 5,6 . Moreover, miR 23a, which contributes to cardiac hyper trophy, was found to protect against muscle atrophy by targeting E3 ubiquitin protein ligase TRIM63 (also known as MURF1) 7,8 .…”
mentioning
confidence: 99%